Comparative study of minimum quantity lubrication and dry drilling of CFRP/titanium stacks using TiAlN and diamond coated drills. (15th February 2020) - Xu, Jinyang; Ji, Min; Paulo Davim, J.; Chen, Ming; El Mansori, Mohamed; Krishnaraj, Vijayan
Abstract: Although minimum quantity lubrication (MQL) has been proved beneficial for the machinability improvement of metallic materials, it is still not well understood whether or not to use the MQL when machining the composite-titanium stacks and whether the MQL can achieve a comparable effect as it operates in the metal cutting processes. The current work is aimed at revealing the underlying mechanisms of the MQL drilling on the CFRP/Ti6Al4V stacks. Both the MQL and dry conditions were examined using the TiAlN-coated and diamond-coated carbide drills to quantify how the MQL operates when compared with the conventional dry machining. The effects of the MQL environment on the machinability of the composite-titanium stacks were quantified in terms of drilling thrust forces, delamination damage of the composite phase and tool wear signatures. A particular emphasis is put on the wettability testing of cut stack hole surfaces versus the minimum quantity lubricants in terms of the contact angle. The results indicate that the machined composite surface shows a strong ability to absorb the lubricants under the MQL condition and fails to form a protective oil film at the drill-chip interface, resulting in an increase of thrust forces and delamination damage. Moreover, the MQL environment cannot prevent the drill bits from premature failures during the machining of CFRP/Ti6Al4V. It is indicated that the MQL fails to yield a comparable beneficial role as it operates in the machining of individual metal alloys in terms of the examined drilling responses.